Climate Risk Management in Agricultural Extension for Ethiopia Facilitators' Guide: 2nd edition - Grossi, Amanda; Dinku, Tufa; Hansen, James; Trzaska, Sylwia; Nsengiyumva, Gloriose; Siebert, Asher; Han, Eunjin; Mangen, Ofelia; Lemma, Esayas; Denboba, Tolessa; Demissie, Teferi; Solomon, Dawit (International Livestock Research Institute, 2024)
This Facilitators’ Guide is an accompaniment to curricular materials presented in the Climate Risk Management in Agricultural Extension Reference Guide and Handbook. This Facilitators’ Guide is intended to be used during implementation of the Climate Risk Management in Agricultural Extension course. This Facilitators’ Guide was designed for use by any trainer or teacher who is implementing the Climate Risk Management in Agricultural Extension course with Ethiopia’s subject matter specialists (SMS) and extension staff, including development agents (DAs). This includes but is not limited to, teachers of Ethiopia’s Agricultural Technical Vocational Education and Training (ATVET) program and its associated colleges. This Facilitators’ Guide was designed to ensure that all of the learning objectives are addressed effectively in the time allotted for each of the four modules that comprise the Climate Risk Management in Agricultural Extension Course. It provides facilitators with a roadmap and step-by-step instructions for each of the modules and their sub- components, including each session’s agenda, presentations, activities, and worksheets. This Facilitators’ Guide is organized by each of the 10 days over which the Climate Risk Management in Agricultural Extension course is implemented and covers the four component modules: Climate Basics, Climate Information Products and Tools Available for Agriculture, Climate-Sensitive Agricultural Decisions, and Integrating Climate Services into Agricultural Extension. The facilitator must juggle many roles within a given session and course, often transitioning seamlessly from one to another or playing multiple roles at a single time. Some effective tips for facilitation and the roles to keep in mind as you prepare to facilitate the course are summarized below.